1993
DOI: 10.1007/bf00012519
|View full text |Cite
|
Sign up to set email alerts
|

Acetobacter diazotrophicus, an indoleacetic acid producing bacterium isolated from sugarcane cultivars of M�xico

Abstract: Thirteen cane cultivars grown on fields in M6xico were sampled to assess the occurrence of Acetobacter diazotrophicus, a recently identified N2-fixing bacterium. Results showed that the isolation frequencies extended over a broad range (1.1 to 67%), likely to be related to the nitrogen fertilization level. The lowest isolation frequencies (1.1 to 2.5%) were obtained from plants growing at high nitrogen doses (275-300 kg ha -~) and the highest values (10-67%) from plants cultivated with 120 kg N ha -~. All eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
0
11

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(111 citation statements)
references
References 25 publications
11
89
0
11
Order By: Relevance
“…A similar pattern was also found in Azotobacter by Sharma et al (2002) and Brown and Walker (1970). Acetobacter diazotrophicus is an IAA-producing bacterium, isolated from sugarcane cultivars of Mexico; it has been suggested that biosynthesis of IAA by bacteria could promote rooting and improve sugarcane growth by direct effect on metabolic processes, in addition to their role in N 2 fixation (Stattar & Gaur 1987, Barbieri & Galli 1993, Fuentes-Ramirez et al 1993, Leinhos & Vacek 1994. Phytohormone synthesized by Azospirillum influenced the root hair development, respiration rate, metabolism and root proliferation, which in turn resulted in better mineral uptake in the inoculated plant (Bar & Okon 1993).…”
Section: Nitrogenase Activitysupporting
confidence: 54%
“…A similar pattern was also found in Azotobacter by Sharma et al (2002) and Brown and Walker (1970). Acetobacter diazotrophicus is an IAA-producing bacterium, isolated from sugarcane cultivars of Mexico; it has been suggested that biosynthesis of IAA by bacteria could promote rooting and improve sugarcane growth by direct effect on metabolic processes, in addition to their role in N 2 fixation (Stattar & Gaur 1987, Barbieri & Galli 1993, Fuentes-Ramirez et al 1993, Leinhos & Vacek 1994. Phytohormone synthesized by Azospirillum influenced the root hair development, respiration rate, metabolism and root proliferation, which in turn resulted in better mineral uptake in the inoculated plant (Bar & Okon 1993).…”
Section: Nitrogenase Activitysupporting
confidence: 54%
“…28,[44][45][46] IAA is a plant growth promoting hormone synthesized by many plant growth promoting bacteria including Gluconacetobacter diazotrophicus. 35,47 In contrast to G. diazotrophicus, G. xylinus does not synthesize IAA; however, exogenously supplied, this hormone greatly influenced growth and development. We observed that when G. xylinus was grown in the presence of IAA, pellicles were thin ( Figure 2A) and of low cellulose content ( Figure 2C).…”
Section: Discussionmentioning
confidence: 99%
“…age) and nitrogen fertilization (FuentesRamírez et al 1993). Remarkably, sensitivity of many diazotrophic bacteria to nitrogen fertilizers could affect their endophytic ability (Fuentes-Ramírez et al 1993, Munõz and Caballero-Mellado 2003, Muthukumarasamy et al 2002, Ramey et al 2004, Tan et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…availability of nitrogen compounds) and especially plant physiology parameters, such as plant age, have strong influence on bacterial response. The exact mechanisms responsible for the plant benefit in different plant-bacteria interactions are not clear, although some evidences point to resistance to diseases (Adhikari et al 2001), increase in available nutrients (CaballeroMellado et al 2004), biological nitrogen fixation (Baldani et al 2000, Baldani andBaldani 2005) and bacterial auxin production (Costacurta and Vanderleyden 1995, Fuentes-Ramírez et al 1993, James et al 2002, Pedraza et al 2004. To study the role of the multifactorial phytohormone auxin/IAA produced by B. kururiensis in our system, the transcriptional regulation of the exogenous auxin-reponsive promoter element DR5 (Scarpella et al 2003) was monitored in rice roots from plantlets infected with the B. kururiensis.…”
Section: Discussionmentioning
confidence: 99%